Evaluasi Mutu Organoleptik dan Tingkat Kesukaan “Morel” Snack Bar Berbasis Tepung Daun Kelor, Apel, dan Mocaf - Putri, Andini Febrita; Mashar, Harlyanti Muthma'innah; Wardani, Rizky Kusuma; Sukrianur, Ahmad (NUTRIASIK: Jurnal Terapan Gizi dan Pangan Fungsional Kesehatan, 2026)
Changes in modern lifestyles have led to increased consumption of convenient snack foods, including snack bars. However, many commercially available snack bars still have limitations in providing balanced nutritional value. The utilization of local food ingredients such as moringa leaf flour, apples, and modified cassava flour (MOCAF) has the potential to improve both the nutritional quality and functional value of snack bars. This study aimed to evaluate the organoleptic quality and consumer acceptance of “Morel” snack bars formulated with combinations of moringa leaf flour, dried apple, and MOCAF. This experimental study employed three formulations: P1 (20%:20%:60%), P2 (15%:25%:60%), and P3 (10%:30%:60%). Organoleptic evaluation included color, aroma, taste, and texture, along with consumer acceptance testing by panelists. Descriptive analysis showed that formulation P1 produced the most intense green color, the strongest grassy aroma, the sweetest taste, and the densest texture. Meanwhile, formulation P2 achieved the highest acceptance scores across all parameters, likely due to its better balance of flavor and aroma. In conclusion, formulation P2 was the most preferred by panelists based on organoleptic quality and consumer acceptance.